OVER ETHNICO – CHARACTERIZATION IN SHAKESPEARE’S OTHELLO, THE MERCHANT OF VENICE AND THE TEMPEST: A CRITICAL ANALYSIS - SOEDE, Casimir Comlan; YEKINI, IBRAHIM (My University, 2018)
Abstract In Othello, The Merchant of Venice and The Tempest, Shakespeare shows that there is a clear opposition between the alien characters represented by Othello, a Black, Shylock, the Jew, a Semite and Caliban, a monster, a savage and the natives, that is to say the European Ones. On the one hand, we have some European characters who stand for the good side of people, the flowers in the garden of human nature, the soul of mankind. On the other hand, the non-European ones who are the symbol of the bad side of humanity, the weeds in the garden of mankind, the dirty body of human nature. Shakespeare has emphasized the white people's qualities and has magnified the vices and weaknesses of aliens, whereas each people has their virtues and flaws. Most of the Europeans are intelligent and educated but none of the outsiders is intelligent and nothing is said about their intellectual level. Résumé L'objet de mon analyse dans cet article est de montrer l'attitude de Shakespeare vis-à-vis des personnages européens et non européens dans Othello, The Merchant of Venice et The Tempest. Dans cet article j'ai démontré que l'écrivain ne traite pas les deux catégories de personnages de la même façon. En effet les premiers sont peints avec indulgence et sympathie. Ils incarnent la bonté de cœur, le courage, l'intelligence. Ils représentent le bien tandis que les seconds sont les plaies de l'humanité. Ils représentent, la laideur aussi bien morale que physique. Tels sont décrits Othello, Shylock et Caliban par le dramaturge. Ce faisant, Shakespeare, par la même occasion, montre que le continent européen est celui des hommes beaux, vertueux alors que le continent africain est celui où les gens comme Othello vivent avec leur vilénie et leurs vices. En d'autres mots, le continent européen représente la blancheur, la lumière tandis que la continent africain représente la noirceur, l'obscurité.
Keywords: Mots clés: intelligence – vertus - imperfections – éducation - nature humaine; Keywords: intelligence – virtues – flaws – education - human nature